Complete sequence of a chicken lambda light chain immunoglobulin derived from the nucleotide sequence of its mRNA. - Reynaud, C A (1983)
Recombinant cDNA plasmids have been constructed from chicken spleen poly(A)-containing RNA. Two clones have been selected and provide the sequence determination of a chicken lambda immunoglobulin light chain: they include the complete variable, constant, and 3' untranslated regions of the chicken lambda light chain mRNA and part of the leader sequence. Comparison of the chicken light chain constant region with both human and mouse lambda constant sequences indicates 61% homology at the amino acid level. Unexpectedly, the chicken variable sequence is 53-63% homologous to human variable sequences when it is compared to the various lambda subgroups and only 42% homologous to the mouse V lambda 1 sequence. The degree of homology between the variable regions of these three species does not easily correlate with their phylogenetic relationship.